Peran Elit Adat dalam Politik Praktis di Sulawesi Selatan Pasca Orde Baru - Sudirman Muhammadiyah (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2013)
The research focused on the provincial executive board of political parties, based in Makassar, while the unit of analysis was five political parties (PAN, PDI-P, PKP, PBB, PKB). This is a qualitative research emphasizing deductive empirical data obtained from interviews with a number of indigenous elites involved in political parties in South Sulawesi, documentation study, and participant observation. The data were then processed and analyzed using the steps, namely: reduction, abstraction, unitization, categorization and coding. Verification on the validity of the data and interpretation using verstehen method indicates that the role of indigenous elites in South Sulawesi is still dominant in political life due to the prevalent paternalistic view in the society. The role can be observed in the activities of political parties in the form of recruitment, mobilization of masses and the establishment of new parties. Similarly, in the efforts to uplift the parties as well as in the conflict resolution, political education, the implementation of the party programs and platforms, the involvement of indigenous elites is rarely absent.Keywords: Indigenous Elite, Political Parties, South Sulawesi